User participation in accounting information system development - A case of ABC Berhad - Mat Saat, Rafeah; Raja Mohd Ali, Raja Haslinda; Yaakub, Nor Asiah (Universiti Utara Malaysia, 2006)
The successful use of a system in an organization depends on the users, their knowledge of the system, their attitudes towards it and the degree to which it matches their perception of the operation.Lack of user participation in information system development (ISD) will result to a failure of a system such as it may not fit users need and may be rejected or under-utilized.Thus users participation in ISD is important not only to developers but to organization to ensure the system is fully utilized by the users and meet the organization objective.Therefore, this study has looked into user participation behavior in ISD.It was conducted to identify the specific participative behavior that was actually used during the system development process and to determine which behavior was most strongly applied in system development process.Data were gathered through on-line survey and analyzed using descriptive analysis.The result showed that in this case study, users participated in all ISD phases, where the highest phase was in project feasibility.